2012
DOI: 10.1177/0022429412462580
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Conductor Facial Expression in Students’ Evaluation of Ensemble Expressivity

Abstract: The purpose of this study was to explore whether conductor facial expression affected the expressivity ratings assigned to music excerpts by high school band students. Three actors were videotaped while portraying approving, neutral, and disapproving facial expressions. Each video was duplicated twice and then synchronized with one of three professional wind ensemble recordings. Participants ( N = 133) viewed nine 1-min videos of varying facial expressions, actors, and excerpts and rated each ensemble’s expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 18 publications
5
31
2
1
Order By: Relevance
“…Numerous researchers have found that delivery skills are important for effective music instruction (Hamann et al, 2000;Hamann & Gillespie, 2012;Johnson et al, 2008;Silvey, 2013). Similarly, the findings I have presented in the present study reinforce the need for inservice and preservice teachers to develop delivery skills.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Numerous researchers have found that delivery skills are important for effective music instruction (Hamann et al, 2000;Hamann & Gillespie, 2012;Johnson et al, 2008;Silvey, 2013). Similarly, the findings I have presented in the present study reinforce the need for inservice and preservice teachers to develop delivery skills.…”
Section: Discussionsupporting
confidence: 80%
“…Research specific to nonverbal instruction in the music classroom encompasses topics related to perceptions of effectiveness (Johnson, Darrow, & Eason, 2008;Silvey, 2013;VanWeelden, 2002), teacher intensity (C. K. Madsen, Standley, & Cassidy, 1989;Yarbrough, 1975), conducting (Byo & Austin, 1994;Worthy, 2006), and modeling (Dickey, 1991;Sang, 1998). Investigations of co-verbal instruction are fewer in number.…”
mentioning
confidence: 99%
“…Both groups reported higher expression ratings for the performances lead by the high expression conductor. Regardless of the type of conductor gesture (positive or negative), observers have reported significantly higher expressivity ratings of their perception of a performance under the direction of expressive conductors compared to neutrally expressive conductors (Silvey, 2013). Although some studies have struggled to find relationships between a conductor's expressive gesture and expression in an ensemble's performance (Price & Chang, 2005;Sidoti, 1990), student musicians have reported a higher preference for an expressive conductor over a conductor with no expressive gestures (Price & Winter, 1991).…”
Section: Conducting Gesturesmentioning
confidence: 96%
“…Even each gaze and facial movement from the conductor can be expressive signals sent to the performers (Poggi, 2002). Although each conductor brings her own musical and instructional gestures to the music creation environment (Garnett, 2005), a wealth of research has found that expressive conducting gestures leads to higher ratings of an expressive performance (Grechesky, 1985;House, 2000;Morrison, Price, Geiger, & Cornacchio, 2009, Silvey, 2013. Morrison and Silvey (2012) investigated the effects of conducting expressivity on choral ensemble evaluation.…”
Section: Conducting Gesturesmentioning
confidence: 99%
“…Forskning på gestikk -dirigentens bevegelser -handler dels om å forstå underliggende virkningsmekanismer, saerlig det som er knyttet til synkronisering av ensemblet (Burger et al, 2014;Luck & Nte, 2008;Luck & Sloboda, 2008;Luck & Toiviainen, 2006). Andre er opptatt av gestikkens ekspressive funksjon (Byo, 1990;Morrison et al, 2014), hvordan gestikken kan understøtte sangernes vokalteknikk (Fuelberth, 2003), eller hvilket kroppsaspekt som virker -hender, blikk og kroppsholdning (Silvey, 2013;Van Weelden, 2002;Wöllner, 2008). Alan Gumm (2018) har undersøkt gestikkens ulike funksjoner og hvordan disse samspiller i dirigentens musikalske ledelse.…”
Section: Tidligere Forskningunclassified